Revisiting the Role of γδ T Cells in Anti-CMV Immune Response after Transplantation - Ahmed Gaballa; Faisal Alagrafi; Michael Uhlin; Arwen Stikvoort (Viruses, 2021)
Gamma delta (γδ) T cells form an unconventional subset of T lymphocytes that express a T cell receptor (TCR) consisting of γ and δ chains. Unlike conventional αβ T cells, γδ T cells share the immune signature of both the innate and the adaptive immunity. These features allow γδ T cells to act in front-line defense against infections and tumors, rendering them an attractive target for immunotherapy. The role of γδ T cells in the immune response to cytomegalovirus (CMV) has been the focus of intense research for several years, particularly in the context of transplantation, as CMV reactivation remains a major cause of transplant-related morbidity and mortality. Therefore, a better understanding of the mechanisms that underlie CMV immune responses could enable the design of novel γδ T cell-based therapeutic approaches. In this regard, the advent of next-generation sequencing (NGS) and single-cell TCR sequencing have allowed in-depth characterization of CMV-induced TCR repertoire changes. In this review, we try to shed light on recent findings addressing the adaptive role of γδ T cells in CMV immunosurveillance and revisit CMV-induced TCR reshaping in the era of NGS. Finally, we will demonstrate the favorable and unfavorable effects of CMV reactive γδ T cells post-transplantation.